The Combination of Doripenem and Colistin Is Bactericidal and Synergistic against Colistin-Resistant, Carbapenemase-Producing Klebsiella pneumoniae - Jernigan, Meredith G. (American Society for Microbiology, 2012)
We tested two-drug combinations of doripenem, colistin, gentamicin, and doxycycline against 12 carbapenemase-producing Klebsiella pneumoniae (KPC) isolates by time-kill. The combination of doripenem and colistin reduced the starting inocula by 2 logs for each isolate (range, 2.02 to 6.01 log(10)) and was bactericidal and synergistic against 75 and 50%, respectively. Among colistin- and pan-drug-resistant isolates, synergy was identified in 60 and 67%, respectively. All other combinations were inferior. We are currently evaluating the combination of doripenem and colistin as a frontline therapy for KPC infection.